2014
DOI: 10.2527/jas.2014-7676
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the laser methane detector to estimate methane emissions from ewes and steers1

Abstract: The laser methane detector (LMD) has been proposed as a method to characterize enteric methane (CH4) emissions from animals in a natural environment. To validate LMD use, its CH4 outputs (LMD-CH4), were compared against CH4 measured with respiration chambers (chamber-CH4). The LMD was used to measure CH4 concentration (µL/L) in the exhaled air of 24 lactating ewes and 72 finishing steers. In ewes, LMD was used on 1 d for each ewe, for 2-min periods at 5 hourly observation periods (P1 to P5, respectively) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 11 publications
(23 reference statements)
6
71
0
1
Order By: Relevance
“…Approximately 13% of CH 4 is produced in the hindgut, where 89% of that (11% of total CH 4 produced) is absorbed into the bloodstream and eliminated via expiration (Ricci et al, 2014).…”
Section: Background On Methodologies For Determining Enteric Methane mentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 13% of CH 4 is produced in the hindgut, where 89% of that (11% of total CH 4 produced) is absorbed into the bloodstream and eliminated via expiration (Ricci et al, 2014).…”
Section: Background On Methodologies For Determining Enteric Methane mentioning
confidence: 99%
“…Methane arises from microbial activities in the lumen of the gastrointestinal tract. The CH 4 produced can be released from the animal via three routes (Ricci et al, 2014): 1) CH 4 from the rumen and lower gut is absorbed into the blood and exhaled from the lungs via expiration, 2) CH 4 emitted directly from the rumen by eructation, and 3) CH 4 emitted from the hindgut in the flatus. Collectively, expiration and eructation have been encompassed in this review by the term "exhaled" gas, as the majority of eructated gas from the rumen is inhaled into the lungs before being exhaled (Hoerneckie et al, 1965;Berends et al, 2014).…”
Section: Background On Methodologies For Determining Enteric Methane mentioning
confidence: 99%
See 2 more Smart Citations
“…Pickering et al (2015) and Paganoni et al (2017) indicated genetic variation and small to moderate heritabilities for CH 4 traits in dairy cows and sheep, and Rösler et al (2018) described an individual variation in enteric CH 4 emissions in female goats. Furthermore, the economic benefits from selection scenarios including CH 4 traits (Robinson and Oddy, 2016) suggest consideration of CH 4 or of CH 4 indicator traits into overall sheep breeding goals.…”
Section: Introductionmentioning
confidence: 99%